EFEKTIVITAS PEMBELAJARAN DARING MENGGUNAKAN LIVEWORKSHEET PADA MATA PELAJARAN BAHASA JERMAN SISWA KELAS X DI SMA NEGERI 1 TAMAN - Alvioniyati, Vindip Tri; Pujosusanto, Ari (LATERNE, 2022)
The Covid-19 pandemic has hampered community activities, including education. The solution from the government so that education can continue is to implement online learning which only requires an internet connection, a device, and a student companion at home. The teacher as the leader of the learning process must strive to help students in order to follow the learning well. One of them is by using Livewoksheet media. Liveworksheet is a platform that can be accessed easily and makes it easy for teachers to evaluate the learning process virtually. This article aims to determine the effectiveness of online learning using Liveworksheet on German language subjects Class X at SMA Negeri 1 Taman. Effectiveness is an attempt to show the level of success in achieving predetermined goals (Handayaningrat, 1996). The method used in writing this scientific paper is a quantitative descriptive instrument in the form of student perception questionnaires and test questions, in order to determine the ability of students after being given treatment with Liveworksheet, with data sources in the form of questionnaires perception and student learning outcomes. The data obtained showed that learning Liveworksheet media on German language subjects in Class X MIPA 3 at SMAN 1 Taman was quite effective. It is known from the results of questionnaires and learning outcomes that show that overall students get an average score of 8.72 with 27 students who completed and 6 students who have not met.